DEVELOPMENT AND VALIDATION OF AN INSTRUMENT MEASURING QUALITY OF LIFE OF WOMEN MICRO ENTREPRENEURS - P, LATHA.; MATHEW, RINCY.V. (International Journal of Psychosocial Rehabilitation, 2020)
Researcher has gone through the published scale. Through a series of revisions and validation processes, identified eight dimensions of Quality of life of women micro entrepreneurs of Kudumbashree each measured with eight, thirteen, and seven items for a total of twenty-five items. Extensive literature review was conducted to identify factors within quality of life. Pilot study was conducted to measure reliability and validity of the instrument. As a result, eight factors were identified. Confirmatory Factor Analysis was done to determine if the data would fit the eight factor structure.